Carbon dioxide thickening: A review of technological aspects, advances and challenges for oilfield application - Pal, Nilanjan; Zhang, Xuan; Ali, Muhammad; Mandal, Ajay; Hoteit, Hussein (Fuel (Guildford), 2022)
[Display omitted] •A review of CO2 thickening as promising technology for oilfield application.•Specific CO2 thickeners eliminate viscous fingering and gravity segregation issues.•CO2 thickeners have been categorized into five types, depending on chemical nature.•Thickening methodology was described to attain optimal viscosity and solubility traits.•It is necessary to develop effective thickeners, while considering cost and toxicity. The relatively low density and viscosity of carbon dioxide (CO2) in supercritical state create several drawbacks, including gravity override, viscous fingering, water production/treatment problems, and poor proppant transport for the petroleum industry. The introduction of CO2 thickeners offers a promising additive technology with sufficient solubility and viscosity enhancement attributes. The current article reviews the technical advances, challenges, and applicability of thickened CO2, particularly for hydrocarbon recovery. Different types of thickeners, including polymers, tailor-made surfactants, and small associating compounds, were investigated in terms of their nature, physicochemical traits, cost, and applications. The molecular weight and concentration, shear rate, co-solvent composition, temperature, and pressure play a significant role in the intermolecular forces and miscibility effect of thickeners in the presence of dense CO2. Binary co-polymers (non-fluorinated non-siloxane materials) and small molecule (associating) compounds are promising options for CO2 thickening owing to their enhanced performance, cost-effectiveness, and low ecological footprint. This study provides a comprehensive review of existing technologies, outline the gaps, potential, and required area for improvement.